La influencia de la lengua inglesa en la crónica social del siglo XIX - Vázquez-Amador, María; Lario-de-Oñate, M. Carmen (Verbum – Analecta Neolatina, 2014)
The press is a reflection of the reality of an era, its society, customs, interests and anything that conveys knowledge of the events happening. This paper aims to examine the Anglicisms related to the social news included in the Spanish press published between the mid 18th century and 19th century. These voices were timidly entering the Spanish newspapers in order to describe the entertainment and the parties high society attended. The Anglicisms will be analyzed in order to determine whether they have lingered into the Spanish language and whether they have been admitted in the different editions of the Royal Spanish Academy Dictionary.